The Future of 3D Brain Cultures in Developmental Neurotoxicity Testing - Hogberg, Helena T.; Smirnova, Lena (Frontiers in Toxicology, 2022)
Human brain is undoubtedly the most complex organ in the body. Thus, it is difficult to develop adequate and at the same time human relevant test systems and models to cover the aspects of brain homeostasis and even more challenging to address brain development. Animal tests for Developmental Neurotoxicity (DNT) have been devised, but because of complex underlying mechanisms of neural development, and interspecies differences, there are many limitations of animal-based approaches. The high costs, high number of animals used per test and technical difficulties of these tests are prohibitive for routine DNT chemical screening. Therefore, many potential DNT chemicals remain unidentified. New approach methodologies (NAMs) are needed to change this. Experts in the field have recommended the use of a battery of human in vitro tests to be used for the initial prioritization of high-risk environmental chemicals for DNT testing. Microphysiological systems (MPS) of the brain mimic the in vivo counterpart in terms of cellular composition, recapitulation of regional architecture and functionality. These systems amendable to use in a DNT test battery with promising features such as (i) complexity, (ii) closer recapitulation of in vivo response and (iii) possibility to multiplex many assays in one test system, which can increase throughput and predictivity for human health. The resent progress in 3D brain MPS research, advantages, limitations and future perspectives are discussed in this review.